Análisis y mejora de los procesos del taller de Ingeniería Industrial en ADELCA Aloag. - Paute Laguatásig, Francisco Javier (2020)
The company Adelca Aloag carries out smelting and processing of steel activities; it has specialized areas to provide support to different departments. The industrial engineering workshop is considered an area that collaborates horizontally with all the departments of the smelter to plan, design, implement and efficiently operate the assignments that require people, materials and tools to avoid delays in the manufacturing and maintenance for parts and to ensure the best performance of systems related to steel production. The workshop has 3 macro processes: maintenance, manufactures, and projects. The main objective of this research is to analyze the processes of the workshop through the application of diagnostic tools to determine the current state and set improvements. The use of inductive and analytical method allows the researchers to start from the analysis of the database from 2018 and 2019 years as well as the application of diagnostic tools: statistical graphs, cause and effect diagram, Pareto diagram, process diagram, and Montecarlo method. Therefore, the results showed the workshop was 43% more productive in 2018 that differs from 2019 because during the second year the workshop was mainly dedicated to maintenance activities being the most critical the repair of panels with fatigue material as the most frequent cause (drastic temperature changes) after that a prediction through the Monte Carlo method of 32 faults for the present year 2020 was made; on the other hand, the time of manufacture of Tundish is reduced by 34%. All detail in this research allows taking decisions to propose improvements for the future of this important area within the smelter.